Pengaruh Perlakuan Panas Karburisasi Austempering Pada Baja Laterit Modifikasi Paduan Ni-Cr Terhadap Sifat Mekanik Dan Struktur Mikro - Satrio Herbirowo (JURNAL POWERPLANT, 2019)
Laterite steel is a steel with a low nickel content which is between 1 - 4.5 percent. Generally, the nickel content in laterite steel which was tried to be developed by LIPI ranged from 1.5 to 4.5 percent. The type of laterite steel developed from laterite ore is NPI (Nickel Pig Iron), a type of cast iron that has a high hardness value and optimal toughness. This material is widely used for grinding balls or Hard-Liner materials for crusher or grinder equipment. In the research of the heat treatment process, Carburization of Austempering uses laterite steel with Ni and Ni-Cr alloys. Where this study uses parameters of heating temperature in the Austenisasi temperature of 950 ºC and Austempering temperature of 400 ºC with the same holding time of 1 hour. In this study also used a variation of cooling media (quenching), namely angina fan, water and left in the furnace. Laterite steel which has been processed by carburization Austempering will be tested by testing hardness, impact, metallography. From the test results obtained test data where, the highest value of hardness is found in steel sample 2 (Ni-Cr), which cooling using a fan with a value of 63.6 HRC with the phase produced martensite. And the highest impact value is found in the sample steel 3 (Ni) which cools in the furnace with an impact value of 38J and the phase formed is bainite.